Ownership Structure, Firm Value And Mediating Effect Of Firm Performance - M. Sahrul; Santi Novita (Jurnal Akuntansi, 2020)
This study aims to examine and analyze the mediating effect of firm performance on ownership structure on firm value. The independent variables are ownership concentration and managerial ownership. The dependent variable is firm value, while the mediating variable is firm performance. The research sample is mining sector companies listed on the IDX in 2016-2018. Data analysis uses Eviews 10. The results show that ownership concentration positively affects company performance, while the opposite results are found in managerial ownership. Then, direct managerial ownership and firm performance positively affect firm value, while ownership concentration does not affect firm value. Firm performance mediates the relationship between ownership concentration and firm value, but firm performance fails to mediate the relationship between managerial ownership and firm value.